Curriculum Management in Lifeskill Development as a Reinforcement of Character Education in Public Elementary Schools in Aceh Tamiang Regency - Afriandi Afriandi; Najmuddin Najmuddin; Mukhlisuddin Mukhlisuddin (Universitas Negeri Malang, 2026)
Abstract: This study aims to analyze the management of character education strengthening curriculum in developing life skills in Public Elementary Schools in Aceh Tamiang Regency. This study is a field research with a qualitative approach. Research informants are based on the strategic role of research subjects in curriculum management in schools. This research was conducted at Public Elementary Schools in Aceh Tamiang Regency. Data collection techniques were carried out through observation, interviews, and documentation review. Data analysis used the stages of reduction, presentation, verification, and drawing conclusions, with validity tests through data and source triangulation, member checks, and observation diligence. The results of the study indicate that: (1) The management of character education strengthening curriculum in Public Elementary School 1 Karang Baru and Public Elementary School Kampung Dalam was implemented with different approaches but both were relevant and had a positive impact on the development of students' life skills. Public Elementary School 1 Karang Baru implemented a systematic approach through formal policies and the integration of character values in the RPP, as well as teacher innovation through Character Roll Calls, Friday Sharing, and Inspiration Classes. Kampung Dalam State Elementary School emphasizes a contextual approach based on local values such as deliberation, politeness, and mutual cooperation through the Village Stories, Inspirational Fridays, and Mutual Cooperation Week programs; (2) The success of the program is determined by the role of the principal and teachers. The principal supports innovation for character building. Teachers,as role models, successfully internalize character and develop students' life skills. The involvement of parents, committees, and the community strengthens the consistency of values and fosters a positive school culture. (3) Character education needs to be contextually adapted to local potential. Reflective, participatory, and contextual curriculum management has proven effective in developing students with character, resilience, adaptability, and competitiveness. Keywords: Curriculum Management; Character Education; Life Skills